PENGHITUNGAN, PENYETORAN, PELAPORAN DAN PENCATATAN PPh 23 PT DEWA DARU ADITECH PRIMA JAKARTA - Nurafni Sabilla Yasin; Featy Octaviany (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the implementation of the calculation, payment, reporting, and recording of Income Tax Article 23 at PT Dewa Daru Aditech Prima Jakarta. The research method used is a descriptive qualitative method with data collection techniques in the form of observation, documentation, and literature study. The data used were obtained from service transactions subject to Income Tax Article 23 during the period of October to December 2025. The results of the study indicate that PT Dewa Daru Aditech Prima has implemented the calculation of Income Tax Article 23 at 2% of the gross amount of service transactions that are subject to tax in accordance with applicable tax regulations. Tax payments were made through an electronic payment system before the specified deadline, and tax reporting was conducted electronically through the Monthly Unified Income Tax Return. In addition, accounting records of transactions subject to Income Tax Article 23 have been carried out systematically in accordance with accounting principles and prevailing tax regulations. Therefore, the implementation of Income Tax Article 23 at PT Dewa Daru Aditech Prima has complied with applicable tax regulations.